Ethno-Religious Issues and Electoral Violence in Sub-Saharan Africa: The Cases of Nigeria and Kenya - Adelana, Olamide S.; Osifo, Kelly Omosat (NIU Journal of Humanities, 2020)
Liberal democracy is characterized by main attributes such as periodic and regular competition for political power with the governed as free agents exercising their free and unfettered choice among competing platforms. Elections have undoubtedly become a significant and crucial pillar in the democratic process since they underscore the principles of political participation, accountability and legitimacy. However, democratic transitions in Africa are historically more complex than in other parts of the world. Specifically, the intersection of politics with ethnicity and religion are perhaps major factors in this regard. For instance, the conduct of elections in plural societies like Nigeria and Kenya are often fraught with animosities and violence. At the core of this bitter contest is the struggle for power by factional elite groups perceived as representing ethno-religious and regional interest. The countriesâ€™ electoral history is replete with narratives of flawed and disputed elections that have turned violent, resulting in numerous fatalities and reversing previous attempts at democratic consolidation. This paper therefore examines the influence of ethnicity and religion on the electoral process in Nigeria and Kenya. It engages the issues or factors that make elections conduct in both countries to be violent prone and undermine attempts at institutionalizing a stable democratic tradition. The paper employs the qualitative and content analysis approach by relying on secondary data from books, journal articles and newspaper commentaries. It affirms that ethnicity and religion play a major role in the elections of both countries and concludes with practicable recommendations. Keywords:  Ethnicity, Religion, Electoral Violence, Nigeria, Kenya, Sub-Saharan Africa